A contribution of fanfiction writing to improving voice and fluency of learners of Japanese from an agentic perspective. (April 2022) - Naderpour, Zeinab
Abstract: This study explores the possibilities of using fanfiction as an out-of-class mediating tool to enhance in-class writing development in distance learning environments. For this purpose, seven Japanese language learners participated in an out-of-class fanfiction writing activity during their spring break. Since the notion of agency is reactive to different learning contexts, it was employed to bridge classroom-based and out-of-class learning practices. To assess learners' level of agency, participant observation and three semi-structured interviews were conducted before, during, and after the fanfiction activity. The data drawn from interviews were analyzed as per the relationships between agency, engagement, self-regulation, autonomy, and investment. First, the issues and stressors that inhibited learners from active participation in in-class learning were identified. Then, a comparison of the agency level regarding learners' in-class practices before and after their participation in the fanfiction activity was made. The results of the analysis indicate that learners' level of agency was developed, and several positive attributes of agentic learners were observed. Furthermore, learners capitalized on affordances of their dynamic interactions with fanfiction writing as they became more fluent in in-class writing and fostered their ability to express their voice. Highlights: The effectiveness of fanfiction writing in JFL learners' voice and fluency is studied. A new model for determining learners' agency level was proposed. The agency model contains engagement, self-regulation, autonomy and investment. Throughout fanfiction activity, the positive characteristics of agentic learners were observed. Compared to the pre-interview results, participants' level of agency has grown significantly.